(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Tetranychus urticae, commonly referred to as the two-spotted spider mite, is one of the most economically damaging pests of agricultural and horticultural crops worldwide. Its polyphagous nature, combined with its exceptional reproductive capacity and short generation time, has contributed to its widespread distribution and pest status in both open-field and greenhouse production systems. In apple orchards, which are economically significant in Uzbekistan and many temperate regions, infestations by T. urticae lead to severe yield and quality losses through leaf chlorosis, bronzing, premature leaf abscission, and reduced fruit development. Compounding this issue is the species’ well-documented ability to rapidly develop resistance to several classes of acaricides, including organophosphates, carbamates, and pyrethroids, making conventional chemical control increasingly ineffective. Consequently, there is an urgent need to implement sustainable management strategies. Integrated Pest Management (IPM) is regarded as the most effective approach to mitigating the pest’s impact while preserving environmental and human health. This thesis systematically reviews the biology, damage mechanisms, and population dynamics of T. urticae, as well as its resistance development patterns, with an emphasis on Uzbekistan’s agro-ecological conditions. The study also evaluates various control methods, including chemical, biological, and cultural practices, highlighting the role of predatory mites such as Phytoseiulus persimilis and entomopathogenic fungi as key biological control agents. The findings indicate that the adoption of IPM strategies, combining selective acaricides, biological agents, and proper cultural practices, can significantly reduce mite populations and mitigate crop damage. This literature-based study aims to support the development of sustainable pest management practices suitable for apple orchards and other susceptible crops in Uzbekistan and similar agro-ecological zones.